1997
DOI: 10.1111/j.1365-2044.1997.101-az0098.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ondansetron and metoclopramide for preventing postoperative emesis following strabismus surgery in children

Abstract: SummaryA double-blind, randomised, placebo-controlled trial was conducted to compare the efficacy of metoclopramide with the 5-HT 3 antagonist, ondansetron, for the prevention of postoperative emesis in children undergoing elective strabismus surgery. None of the children received any premedication and a similar anaesthetic technique was used for all. Ondansetron 0.15 mg.kg ÿ 1 , metoclopramide 0.25 mg.kg ÿ 1 or saline placebo were administered following intravenous catheter placement. Episodes of emesis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29] Other studies reported efficacy of the drug in pediatric surgical or oncology patients. [30][31][32][33][34][35][36][37][38][39] One of those studies reported mild, asymptomatic QT prolongations that remained within normal limits. 31 A literature search was performed for reports of ventricular arrhythmias, fatalities, or any type of toxicity thought to be related to ondansetron in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Other studies reported efficacy of the drug in pediatric surgical or oncology patients. [30][31][32][33][34][35][36][37][38][39] One of those studies reported mild, asymptomatic QT prolongations that remained within normal limits. 31 A literature search was performed for reports of ventricular arrhythmias, fatalities, or any type of toxicity thought to be related to ondansetron in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…[54] Other studies have shown that the antiemetic effect of ondansetron persists for up to 24 hours following surgery. [55][56][57][58][59] The incidence of late-onset PONV (>4 to 24 hours) was not influenced by prophylactic treatment with one dose of ondansetron preoperatively. [60] Ondansetron, at doses varying from 40 to 200 μg/kg, administered IV after induction in children undergoing strabismus surgery reduced the risk of vomiting, particularly in the group receiving the highest dosage.…”
Section: Ondansetronmentioning
confidence: 95%
“…Postoperative nausea and vomiting remains a significant morbidity problem after general anaesthesia and the 5-HT3 antagonists have been shown to be at least as effective as standard antiemetics but with an improved side effect profile 34 35. Postoperative nausea and vomiting remains a problem, however, and ongoing studies are investigating the efficacy of combination therapy (antagonising more than one receptor type) and the activity of the new neurokinin type 1 receptor antagonists.…”
Section: Postoperative Emesismentioning
confidence: 99%